2010
DOI: 10.1111/j.1939-1676.2010.0516.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I in Doberman Pinschers with Cardiomyopathy

Abstract: Background: Cardiac troponin I (cTnI) is useful for detection of cardiac myocyte damage, but its efficacy in detecting various stages of dilated cardiomyopathy (DCM) in Doberman Pinschers is unclear.Objectives: To evaluate the diagnostic value of cTnI in various stages of DCM in Dobermans. Animals: Six hundred and fifty-three cTnI measurements of 336 Doberman Pinschers. Methods: Using a longitudinal study design, staging of the disease was based upon 24-hour-ambulatory-ECG (Holter) and echocardiography. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 44 publications
9
41
0
5
Order By: Relevance
“…Other types of heart disease may affect cTnI concentrations . Increased cTnI concentrations have been reported in dogs with mitral valve disease, cardiomyopathy, and cardiac hemangiosarcoma . The cTnI concentration may support echocardiographic data but cannot be used alone to diagnose any cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of heart disease may affect cTnI concentrations . Increased cTnI concentrations have been reported in dogs with mitral valve disease, cardiomyopathy, and cardiac hemangiosarcoma . The cTnI concentration may support echocardiographic data but cannot be used alone to diagnose any cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in human and veterinary medicine have demonstrated that serum cardiac troponin concentrations are increased in various cardiac and noncardiac diseases 4, 19, 30, 33, 38, 44, 45…”
Section: Discussionmentioning
confidence: 99%
“…Based on this information, we did not exclude dogs with renal failure. The study should include all feasible medical ICU patients, excluding those with cardiac disease, but renal failure as well as age29, 30, 48 and extensive physical strain should be kept in mind as differentials for increased cTnI concentrations 49…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this finding remain unclear, but might involve interday variability in arrhythmia severity, the relatively low number of ventricular arrhythmias present in any individual dog, and the fact that blood sampling for NT‐proBNP assay was not performed simultaneously using Holter examination. Alternate biomarkers of cellular damage, electrical dysfunction, or arrhythmias, such as cardiac troponin, might be superior or complementary to NT‐proBNP assay in detecting H‐ODCM …”
Section: Discussionmentioning
confidence: 99%